Fractional-order systems and PID controllers : using Scilab and Curve fitting based approximation techniques /: using Scilab and Curve fitting based approximation techniques. ([2020]) - Bingi, Kishore; Ibrahim, Rosdiazli; Karsiti, Mohd Noh; Hassan, Sabo Miya; Harindran, Vivekananda Rajah
No abstract available